An Analysis Upon Determinants of Nutritional Health Status of School Age Children In India: Exploring the Prevalence and Impact of Malnutrition on School Age Children in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The health and nutritional status of children is an index of nationalinvestment in the development of its future manpower. Malnutrition affects thechild’s physical and cognitive growth and increases the susceptibility toinfections while having an adverse impact on economic growth of the countryindirectly. With 40% of the world’s malnourished living in India, we face adouble jeopardy of malnutrition. School children from various primary andmiddle level educational facilities from a rural health block were surveyedduring the School Health Program. Height and weight was measured followingstandard procedures. Under-nutrition continues to be a primary cause of ill health andmortality among children in developing countries. Besides poverty, there areother factors that directly or indirectly affect the nutritional status ofchildren. In the present study, an attempt was made to find the prevalence ofunder-nutrition among school children and the role of socio-demographiccharacteristics of mother on child nutrition. Malnutrition is a gravethreat to maternal and child health across the world with its most of thevictims observed in the developing nations. It is the condition that resultsfrom consuming a diet in which certain nutrients are lacking. A miserablepicture of malnutrition and under-nutrition is prevalent among mothers andchildren in rural areas on one hand and slums and shanties of the urban areason the other in India as well as in the state of West Bengal. Kwashiorkor,Marasmus, Rickets are the common diseases seen among children due tomalnutrition. A number of nutritional deficiency syndromes tend to affect theoverall physical and mental development making the child susceptible to variouschildhood diseases. Children living in the unhygienic slum areas cursed withmalnutrition are vulnerable to pediatric tuberculosis as well. Early marriagecoupled with early pregnancy, improper feeding habits, inadequate diet andnegligence culminates into signs and symptoms of malnutrition among pregnantwomen, the result of which is reflected after birth of the infant who is alsovulnerable to inherit symptoms of malnutrition, under-nutrition and anaemia.